Relationship of Bone Densitometry and Bone Resorption Markers With Menopausal Type and Duration - Nermin Akdemir,; Cemil Bilir,; Hakan Cinemre,; Muhittin Pekuz,; Feyzi Gökosmanoğlu, (Archives of Rheumatology, 2010)
Objective: Menopause age and bone mineral density are positively related and there is a rapid bone loss in the early post-menopausal period. A ratio of 30% of post-menopausal women are affected from osteoporosis developing due to bone loss and this causes 40% risk of fracture in a 50- year old woman. Materials and Methods: In this sudy, serum osteocalcin and urine deoxypridinoline levels were analyzed in 102 postmenapausal and 48 healthy premenopausal controls who presented to gynecology outpatient clinic. Bone densitometry was obtained from all postmenopausal women. Postmenopausal patients were further divided into four groups according to time since menopause: <5 years, 5-9 years, 10-19 years and >20 years. Results: Mean (SD) age in 48 premenopausal women was 47.7 (3.7) while it was 56.5 (6.8) in 102 post-menopausal women. 34 out of 102 post-menopausal women had surgical menopause due to bilateral oopheroctomy+hysterectomy while the remaining had natural menopause. No significant difference was found in bone-turnover markers between women with surgical and natural menopause. Conclusion: Although there was not a statistically significant difference between bone-turnover markers, bone mineral density stays lower in surgical menopausal patients and this difference disappear only after about 20 years. Also bone turnover markers are usually high up to five years after surgical menopause and return to normal levels after then. Thus, our study suggested that oopheroctomy does not cause additional risk to hysterectomy. We also suggest that there is not a long-term relationship between serum bone turnover markers or bone density and the etiology of menopause. (Turk J Rheumatol 2010; 25: 29-33)